The Boxcar Children : The Haunted Cabin Mystery - Book 20 - Limke, Jeff; Bloodworth, Mark; Warner, Gertrude Chandler, 1890-1979. (Morton Grove, Ill. : Albert Whitman, 2009)
The Alden children travel on a Mississippi paddle-wheel steamer to visit an old family friend in his cabin near Hannibal, Missouri, and try to discover who is responsible for the mysterious activities near the house.
At head of title: Gertrude Chandler Warner's the boxcar children.
Keywords: Siblings -- Fiction; Orphans -- Fiction; Buried treasure -- Fiction; Friendship -- Fiction; Mississippi River -- Fiction; Fiction; Graphic novels